Secreto a voces. ¿La ascensión presidencial de Mike Pence? - Cisneros Tirado, José A.; Navarro Sequeira, Melva G.; Scherlen, Renee (El Colegio de México A.C., 2018)
How likely is it that President Trump will not serve his full term? Donald Trump ran a highly contentious political campaign; many of his messages could be identified as xenophobic, misogynist or racist. After becoming the 45th president of the United States, many political observers expected his initial actions would be less controversial, thus setting a more compromising tone for his government. However, this has not happened. President Trump signed more than sixty executive orders, which rolled back on some of the most prominent government actions implemented by the Obama administration. President Trump is also spearheading changes aimed at modifying the economic and geopolitical landscape by loosening Wall Street and environmental regulations, altering the tax code, banning immigration from several Muslim-majority countries and continuing plans to build a border wall. In addition, the Administration has become mired in a scandal regarding its potential links between the presidential campaign and the Russian government. According to Section 4 of the 25th amendment of the Constitution of the United States, if the Vice President and a simple majority of the Cabinet deem the President unable to discharge the powers and duties of his office, the Vice President becomes Acting President. Another possible scenario could lead to impeachment based on conflict of interests or misuse of Presidential power. Again, the result of successful impeachment would be Mike Pence assuming the residency. Our paper analyzes various possible scenarios regarding prospective challenges to the continuation of President Trump in office. The purpose of the paper is to assess the relative likelihood of different paths to power for Mike Pence.